On the ethics of high stakes hide and go seek: a response to James Beilby - Rizzieri, Aaron (International journal for philosophy of religion, 2025)
Aaron Rizzieri has argued that the problem of divine hiddenness is exacerbated in any theistic tradition which entails that people may experience negative afterlife consequences engendered by a failure to know God exists and relate to God properly. (2021) James Beilby has countered by suggesting an afterlife choice model according to which everyone will have a robust opportunity post-mortem to freely choose to be in relationship with the divine. (2023) I defend Rizzieri’s position against this counterargument on the grounds that it is implausible that everyone will retain their libertarian freedom to be in relationship with the divine no matter what experiences they have had and attitudes they have cultivated in this life.